(untitled) (INNOVATIVE ECONOMY, 2020)
Shkilnyak М.М. THE CRITERIA FOR EFFECTIVE MANAGEMENT OF THE COMMUNAL PROPERTY OF TERRITORIAL COMMUNITIES Purpose. The objective of the article is to study and determine the criteria for effective management of communal property of territorial communities. Methodology of research. The information base of the research is the principles of the economic theory, the Laws of Ukraine, the materials of the State Property Fund of Ukraine, the statistical bodies, the results of researches of scientists and practitioners on communal property issues. To achieve this aim, general scientific and special methods of research were used, namely historical and logical methods (in the study of the evolution of communal property management problems), comparative analysis (in the selection and application of methods of using communal objects) and system analysis (for the formation of a mechanism of communal property management). Findings. After analyzing the state of utilization of communal property, the main factors influencing its effective use are determined. It is proved that the problem of effective management of objects of communal property is investigated insufficiently. Within the framework of the research, the essence of the category "effective use of property" is determined. Summing up foreign and domestic practice, the structure of the program of management of communal property was formed. According to the results of the study, approaches and criteria for assessing the effectiveness of using communal property by the executive bodies of territorial communities are proposed. Originality. Methodical approaches to the economic evaluation of the effective use of communal property are proposed. Groups of criteria for assessing the effectiveness of managing the property of communal property of territorial communities are formed. Practical value. The results of the research and the proposals on the effective use of communal property are aimed at increasing the financial capacity of the territorial communities. Key words: municipal property; assessment; efficiency; local self-government; territorial communities; criteria; decentralization.